IMPLEMENTASI SLOGAN "JABAR JUARA" DALAM CITY BRANDING SEKTOR PARIWISATA BERBAGAI KOTA DI JAWA BARAT - Susilowati Susilowati; Devy Putri Kussanti (JURNAL TRIAS POLITIKA, 2023)
ABSTRACTWest Java Province uses the slogan "Jabar Champion" as a city branding step with the aim of achieving West Java Champion both physically and mentally, through innovation and collaboration, namely to realize the 9 main program missions of RINDU, and the fourth mission is "to increase the productivity and competitiveness of the national economy prosperous and just by using digital technology and collaborating with centers of innovation and development activities, one of which is "Tourism Champion". This research is to see how a series of activities to realize the slogan "Jabar Champion" to realize the city branding of several cities in West Java in the tourism sector. The research uses descriptive research methods with qualitative data analysis, with in-depth interpretation based on existing literature. The research tradition used is documentary analysis to analyze documents/libraries in depth to find out the meaning behind the literature. The results of the research are the development of tourism in the West Java region in accordance with the slogan "West Java Champion" a lot of development has been carried out in the tourism sector in accordance with what is contained in the details of the fourth mission in the main program of RINDU and one of them is the 5 programs in "Tourism Champion" all of which have carried out by the West Java Provincial Government, but in the fifth program there is still not much development of tourism human resources available. As the application of the three key strategies in carrying out city branding in the tourism sector, of the three key City Branding strategies, there are still many reports that broadcast about problems that occur in newly inaugurated tourist attractions.ABSTRAKProvinsi Jawa Barat menggunakan slogan “Jabar Juara” sebagai langkah branding kota dengan tujuan untuk meraih Jawa Barat Juara lahir dan batin, melalui inovasi dan kolaborasi, yaitu untuk mewujudkan 9 misi program utama RINDU, dan misi keempat adalah “meningkatkan produktivitas dan daya saing perekonomian nasional yang sejahtera dan berkeadilan dengan menggunakan teknologi digital serta berkolaborasi dengan pusat-pusat inovasi dan kegiatan pembangunan, salah satunya “Pariwisata Juara”. penelitian ini  untuk melihat bagaimana sebuah rangkaian dari aktifitas guna mewujudkan slogan “Jabar Juara” untuk mewujudkan city branding beberapa kota di Jawa Barat  dalam sektor pariwisata. Penelitian menggunakan metode penelitian deskriptif dengan analisa data kualitatif, dengan interpretasi mendalam berdasarkan studi pustaka yang ada. Tradisi penelitian yang digunakan ialah documentary analysis guna menganalisis dokumen/pustaka secara mendalam untuk mengetahi makna dibalik pustaka tersebut. Hasil penelitian yaitu pengembangan wisata di wilayah Jawa Barat sesuai dengan slogan “Jabar Juara” telah banyak dilakukan pengembangan sector wisata sesuai dengan apa yang terdapat pada rincian dari misi keempat dalam program utama RINDU dan salah satunya adalah 5 program dalam  “Pariwisata Juara”  yang kesemuanya telah dilakukan oleh Pihak Pemerintah Provinsi Jawa Barat, akan tetapi pada program kelima masih belum banyak tersedianya pengembangan sumber daya manusia pariwisata. Sebagai penerapan tiga kunci strategi dalam melakukan branding kota dalam sektor pariwisata, dari ketiga kunci strategi City Branding tersebut masih banyaknya pemberitaan yang menyiarkan mengenai permasalahan yang terjadi pada tempat wisata yang baru diresmikan.